Needs and skills for a national manpower force - D.J.J. van Rensburg; G.J. Brink (Koers : Bulletin for Christian Scholarship, 1995)
South Africa has been isolated from external business competition for many years. The political changes under way in the Republic are bringing with them the reality of international competition from world class players. In order to compete and survive, more attention will have to be devoted to the composition and quality of the South African work force. Education needs to be made more relevant to employment in terms of the skills required by the modern economic society. The workers of tomorrow will require a different and more sophisticated knowledge and skills portfolio than the workers of today and yesterday. An analysis of the needs and skills for a national manpower force is therefore appropriate.